Acellular Nerve Allografts in Major Peripheral Nerve Repairs: An Analysis of Cases Presenting With Limited Recovery. (March 2023) - Peters, Blair R.; Wood, Matthew D.; Hunter, Daniel A.; Mackinnon, Susan E.
Background: Acellular nerve allografts have been used successfully and with increasing frequency to reconstruct nerve injuries. As their use has been expanded to treat longer gap, larger diameter nerve injuries, some failed cases have been reported. We present the histomorphometry of 5 such cases illustrating these limitations and review the current literature of acellular nerve allografts. Methods: Between 2014 and 2019, 5 patients with iatrogenic nerve injuries to the median or ulnar nerve reconstructed with an AxoGen AVANCE nerve allograft at an outside hospital were treated in our center with allograft excision and alternative reconstruction. These patients had no clinical or electrophysiological evidence of recovery, and allograft specimens at the time of surgery were sent for histomorphological examination. Results: Three patients with a median and 2 with ulnar nerve injury were included. Histology demonstrated myelinated axons present in all proximal native nerve specimens. In 2 cases, axons failed to regenerate into the allograft and in 3 cases, axonal regeneration diminished or terminated within the allograft. Conclusions: The reported cases demonstrate the importance of evaluating the length and the function of nerves undergoing acellular nerve allograft repair. In long length, large-diameter nerves, the use of acellular nerve allografts should be carefully considered.